1996
DOI: 10.1093/nar/24.4.694
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Type of Retinoic Acid Response Element in the Second Intron of the Mouse H2Kb Gene is Activated by the RAR/RXR Heterodimer

Abstract: We have identified and characterized a novel retinoic acid (RA) response element (Hi-RARE) in the second intron of the mouse major histocompatibility H2Kb gene. The Hi-RARE sequence is conserved in all mouse classical and Q class 1 genes, in MHC class 1 genes of the rat, Rhesus macaque, cat and in the vast majority of human classical and non-classical class 1 genes. The Hi-RARE sequence lies within a regulatory element responsible for constitutive expression of a 5' enhancerless H2Kb gene in the Ltk-fibroblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…Furthermore, using Vil1 -cre- Rara fl/fl mice we found that atRA treatment directly acts on tumor epithelial cells to upregulate MHCI expression, thereby rendering them more susceptible to killing by CD8 + cytotoxic T lymphocytes. Consistent with this mechanism, previous in vitro studies have demonstrated that MHCI is a direct transcriptional target of atRA (Balmer and Blomhoff, 2002; Jansa and Forejt, 1996; Nagata et al, 1992). Untreated Vil1 -cre- Rara fl/fl mice induced with AOM-DSS did not develop more tumors than control mice, but since mice with CAC already have dramatically reduced levels of atRA, the absence of RARα on epithelial cells likely would have had little impact on tumor burden.…”
Section: Discussionsupporting
confidence: 68%
“…Furthermore, using Vil1 -cre- Rara fl/fl mice we found that atRA treatment directly acts on tumor epithelial cells to upregulate MHCI expression, thereby rendering them more susceptible to killing by CD8 + cytotoxic T lymphocytes. Consistent with this mechanism, previous in vitro studies have demonstrated that MHCI is a direct transcriptional target of atRA (Balmer and Blomhoff, 2002; Jansa and Forejt, 1996; Nagata et al, 1992). Untreated Vil1 -cre- Rara fl/fl mice induced with AOM-DSS did not develop more tumors than control mice, but since mice with CAC already have dramatically reduced levels of atRA, the absence of RARα on epithelial cells likely would have had little impact on tumor burden.…”
Section: Discussionsupporting
confidence: 68%
“…A novel RARE has been identified in the downstream responsive element of the mouse H2Kb gene and found to be highly conserved in MHC class I genes [49]. The outer repeat sequences are present and unmutated in all 16 classical MHC class I genes in mice, and the intact RARE is also conserved in other mammalian species [49].…”
Section: Rarγ and The Cd8 T Cell Responsementioning
confidence: 99%
“…The outer repeat sequences are present and unmutated in all 16 classical MHC class I genes in mice, and the intact RARE is also conserved in other mammalian species [49]. …”
Section: Rarγ and The Cd8 T Cell Responsementioning
confidence: 99%
“…The extracts were stored at 280°C. The EMSA experiments were performed as described (Jansa and Forejt, 1996), with small modifications. Briefly, DNA fragments were end-labeled by filling-in with [a-32 P]dATP using Klenow (Fig.…”
Section: Electrophoretic Mobility-shift Assay (Emsa)mentioning
confidence: 99%